Management - Alekseieva, Kateryna; Holeva, Mariia (My University, 2023)
The course of lectures is designed to consolidate the theoretical and practical foundations of enterprise management, which consistently considers all aspects, categories and provisions of management, namely: the essence of management, the importance of manager and manager, the evolution of management, types of organizations as objects of management, the management process, functions and methods of management, management decisions, communications, leadership in the system of management functions, organizational changes and organizational development, formation of a labour collective, self-management, etc. For students of specialty 073 "Management".
Recommended by the Academic Council of the Faculty of Agrarian Management of the NULES of Ukraine
Keywords: Management; Менеджмент